The balance-sheet of the Bank of Italy - L. MAGNANI (PSL Quarterly Review, 2014)
The article describes the nature and consistency of the several items on the balance-sheet of the Bank of Italy, as they have developed in the past ten years, during which economic vicissitudes have led to important alterations in its construction.